A Study of Livestock Management Patterns in Sagarmatha National Park, Khumbu Region: Trends as Affected by Socio-Economic Factors and Climate Change - Sherpa, Yangji Doma; Kayastha, Rijan Bhakta (Kathmandu University Journal of Science, Engineering and Technology, 2009)
The landscape of Sagarmatha National Park (SNP) evolved under centuries of livestock grazing and farming activities of the Sherpa people. This study attempts to determine changes in livestock population and composition, and explore major driver of changes in the six major year-round settlements in SNP that will be helpful to introduce management interventions for sustainable level of farming in the Park. The necessary data are collected through questionnaire survey. The study indicates that the total number of livestock in Khumbu has not declined, but their type and distribution have changed in each settlement over time. The male cattle breeds are increasing as these animals are used as pack animals and make twice the income of a human porter. However, female cattle breeds are declining because of the meager returns. Likewise, the number of livestock is comparatively less in places like Namche and Khumjung which are on the main tourist route, while in places like Forste and Thamicho where tourism flow is comparatively less, livestock number is high. As tourism created many employment opportunities with substantial income, people are gradually scaling down yak farming. Though tourism is the main driver of changes in livestock patterns, there are other socio-economic factors like education, prestige, political change, and globalization which have modified the animal husbandry practices. Increasing atmospheric temperatures, changes in precipitation patterns, and increased frequency of extreme weather events are the climatic changes seen in the area which are the result of climate change. But the socio-economic factors have actually outweighed the impacts of climate change on livestock in the area. However, as global warming continues, changing climatic patterns could possibly affect high altitude indigenous breeds like yak by creating shortage of water, fodder and increase in pests and diseases.